The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1302/2046-3758.710.bjr-2018-0015.r2
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic and antiresorptive actions of locally delivered bisphosphonates for bone repair

Abstract: During the last decades, several research groups have used bisphosphonates for local application to counteract secondary bone resorption after bone grafting, to improve implant fixation or to control bone resorption caused by bone morphogenetic proteins (BMPs). We focused on zoledronate (a bisphosphonate) due to its greater antiresorptive potential over other bisphosphonates. Recently, it has become obvious that the carrier is of importance to modulate the concentration and elution profile of the zoledronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 86 publications
0
10
0
1
Order By: Relevance
“…Bisphosphonates are viewed as capable of enhancing the intrinsic anabolic potential of bone, 22 and our intention to protect newly formed bone was reached with systemic zoledronate, despite low values of retained allograft, normally viewed as a lattice for new bone formation. 23 No significant anabolic effect of rhBMP-2 irrespective of zoledronate administration route was seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bisphosphonates are viewed as capable of enhancing the intrinsic anabolic potential of bone, 22 and our intention to protect newly formed bone was reached with systemic zoledronate, despite low values of retained allograft, normally viewed as a lattice for new bone formation. 23 No significant anabolic effect of rhBMP-2 irrespective of zoledronate administration route was seen.…”
Section: Discussionmentioning
confidence: 99%
“…The larger surface area of new bone with local zoledronate compared to systemic zoledronate may stem from a peripheral effect by zoledronate eluting from allograft, as seen with bisphosphonate-augmented implants. 22 With systemic zoledronate, bone mineralization may not have been extensive enough at zoledronate administration points, or zoledronate, a high affinity bisphosphonate, was bound peripherally in the grafted gap leaving the surface unprotected. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there have been different studies targeting bone formation-related pathways such as the BMP signalling pathway. 84 , 85 The tight interaction between the immune system and the skeletal system has been recognized in the emerging research field of osteoimmunology. 86 Thus, the inflammatory response could also be one potential target for immune-modulatory approaches to enhance fracture healing, as a previous study demonstrated that modulation of inflammatory reaction could enhance osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the antiresorptive bisphosphonates available today, those containing nitrogen in the heterocyclic ring, for example zoledronic acid, are 10,000 times more potent than non-nitrogen-containing bisphosphonates. 25 , 26 Bisphosphonates are today widely used for retarding osteoporosis by acting on osteoclasts and slowing bone resorption. 25 , 27 …”
Section: Hydroxyapatite As a Drug-seeking Moietymentioning
confidence: 99%